Novel Osteobiologics and Biomaterials in the Treatment of Spinal Disorders. Issue 3 (21st February 2017) - Hsu, Wellington K.; Goldstein, Christina L; Shamji, Mohammed F.; Cho, Sam K.; Arnold, Paul M.; Fehlings, Michael G.; Mroz, Tom E.
Abstract: Spinal osteobiologics have evolved substantially in this century after the development of many product categories such as growth factors, allograft, and stem cells. The indications for the use of novel biologics within spine surgery are rapidly expanding as the mechanism of each is elucidated. While the knowledge base of bone morphogenetic protein increases with each subsequent year, the application of new nanotechnology and cell-based strategies are being reported. This review will discuss the most recent data in novel osteobiologics, and where we could use future study.